Replacement of rice bran with pleurotus florida stalks on growth performance of oreochromis niloticus fingerlings - Hasniyati Muin; Nurul Nadwa Abdul Fatah; Izzat Hamdi Bahari; Shaharudin Abdul Razak (Universiti Kebangsaan Malaysia, 2014)
A 6-weeks feeding experiment was conducted to evaluate the effect of replacement of rice bran with mushroom stalk (Pleurotus florida) an agriculture waste, on growth performance in tilapia fingerlings (Oreochromis niloticus). Three isonitrogenous (32% crude protein) diets were formulated. Rice bran was replaced with 100% (Diet 1), 50% (Diet 2) and 0% (Diet 3, control) mushroom stalk. Each dietary treatment was tested in triplicate group of 12 fingerlings per tank arranged in completely randomized design. The result of this study showed that there was no significant difference (p>0.05) among all diets in terms of growth performance and feed utilization. Diet 1 gave the best results in BWG, SGR, FCR and PER. An economic evaluation indicated that Diet 1 gave the lowest production cost at RM2.03/kg followed by Diet 2 (RM2.18/kg) and Diet 3 (RM2.38/kg). Taking all the factors into consideration, the best diet was Diet 1 with 100% replacement of rice bran with mushroom stalks which is also the cheapest diet. This shows that Pleurotus florida stalks can replace 100% of rice bran in practical tilapia diets.